CHALLENGES AND STRATEGIES IN ENHANCING TAX COMPLIANCE AUDITING: A PHENOMENOLOGICAL STUDY OF TAX AUTHORITY AUDITORS - Rosli, Farah Nor Aishah (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
Tax compliance auditing is essential to maintaining economic stability and promoting trust in tax systems. This study examines the challenges faced by tax authority auditors and identifies strategies to improve compliance practices. Using a qualitative phenomenological approach, data were collected through structured interviews with ten experienced auditors. The thematic analysis revealed three core themes: regulatory complexity, operational constraints and transparency issues. The results highlight the significant burden on auditors caused by rapidly evolving tax laws, high caseloads and inadequate cooperation from companies. Practical recommendations include structured training, simplified procedures guidelines and technological integration to improve audit efficiency. This study contributes to the growing discourse on tax compliance by providing actionable insights based on the experiences of selected tax auditors in Malaysia.